Neural crest and placodes - Trainor, Paul A. (Current topics in developmental biology ;, 2015)
Neural Crest and Placodes provides in-depth coverage of the topic, including information on their critical role in vertebrate development, evolution, and the way defects in their development underlie a wide range of congenital disorders. It delves deep into advances made in our understanding of the mechanisms governing the formation, migration, and differentiation of these two cell populations, also discussing their integration during embryonic development. The text highlights the application of fundamental knowledge in investigating the etiology and pathogenesis of congenital disorders an.